Peran Ekspektasi atas Pendapatan dan Konsep Diri dalam Memperkuat Hasrat untuk Memulai Berwiraswasta - Sutejo, Bambang (Keizai, 2020)
This study aims to determine the effect of expectations on income and self-concept on the desire to start an entrepreneur. The population in this study were active students of the Faculty of Business and the Faculty of Computer Science, Darwan Ali University. Data analysis used descriptive statistical analysis, prerequisite test analysis, and multiple linear regression analysis. The results showed that (1) Expectations on Income had a positive and significant effect on the Desire to Start Entrepreneurship which was indicated by a significance valueless than the level of significance (0.000 <0.050) and the t value of 9.437 which was greater than the t table. (2) Self-concept has a positive and significant effect on the Desire to Start Self-Employment, which is indicated by a significance value less than the level of significance (0.000 <0.050) and the t-count value of 9.437 is greater than the t table. (3) Expectations on Income and Self-Concept simultaneously have a positive and significant influence on the desire to start Self-Employment.